Neurophysiological investigations of drug resistant epilepsy patients treated with vagus nerve stimulation to differentiate responders from non‐responders. (19th May 2020) - Hödl, S.; Carrette, S.; Meurs, A.; Carrette, E.; Mertens, A.; Gadeyne, S.; Goossens, L.; Dewaele, F.; Bouckaert, C.; Dauwe, I.; Proesmans, S.; Raedt, R.; et al.
Abstract : Background and purpose: In patients treated with vagus nerve stimulation (VNS) for drug resistant epilepsy (DRE), up to a third of patients will eventually not respond to the therapy. As VNS therapy requires surgery for device implantation, prediction of response prior to surgery is desirable. It is hypothesized that neurophysiological investigations related to the mechanisms of action of VNS may help to differentiate VNS responders from non‐responders prior to the initiation of therapy. Methods: In a prospective series of DRE patients, polysomnography, heart rate variability (HRV) and cognitive event related potentials were recorded. Polysomnography and HRV were repeated after 1 year of treatment with VNS. Polysomnography, HRV and cognitive event related potentials were compared between VNS responders (≥50% reduction in seizure frequency) and non‐responders. Results: Fifteen out of 30 patients became VNS responders after 1 year of VNS treatment. Prior to treatment with VNS, the amount of deep sleep (NREM 3), the HRV high frequency (HF) power and the P3b amplitude were significantly different in responders compared to non‐responders ( P  = 0.007; P  = 0.001; P  = 0.03). Conclusion: Three neurophysiological parameters, NREM 3, HRV HF and P3b amplitude, were found to be significantly different in DRE patients who became responders to VNS treatment prior to initiation of their treatment with VNS. These non‐invasive recordings may be used as characteristics for response in future studies and help avoid unsuccessful implantations. Mechanistically these findings may be related to changes in brain regions involved in the so‐called vagal afferent network.